(3GdYLGdgs
(3ChdgG (B:s
(3Cfg cGf EPG aYd ef ML Ch YeQI cHQ Ydi cd ecGf eQJaY KdGKkG Ke bGd dG Edg EdG Gddg hMOg dGTQjc dg dg Gdedc hdg GdMeO hgh Ydi cd TF bOjQ s
(3BNQgG (B:s
(3hEf cGf MQGekG Ydi GdPejI MQe Ydi GdeSdeg GdJecjf efg hojMJed Cfg CQGO GdJMQje Ydi GdeSdeg hgh XGgQ cJGH YeQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs